Phytoseiidae (Acari: Mesostigmata) in four provinces of Iran - Azadeh Farazmand; Mahdi Jalaeian; Hashem Kamali; Alireza Saboori; Marie-Stéphane Tixier; Serge Kreiter (Persian Journal of Acarology, 2023)
The present study reports the results of surveys carried out over a period of two years (2018 and 2020) in four provinces of Iran: Guilan, Razavi Khorasan, Mazandaran, and Sistan and Baluchestan. Twenty-three species from eight genera of Phytoseiidae have been collected, of which two species were newly recorded for Iran, namely: Euseius gallicus and Proprioseiopsis lineatus. Three species, namely Neoseiulus agrestis, Amblyseius obtusus, Typhlodromus (Anthoseius) haiastanius are new records for the Guilan Province. Neoseiulus californicus and Amblyseius swirskii are new records for the Mazandaran Province while Typhlodromus (Anthoseius) haiastanius is a new record for the Razavi Khorasan Province. All species collected in Sistan and Baluchestan are new records for this province. The worldwide distribution and plant hosts of all collected phytoseiids during this study are provided.